Kemampuan Pemecahan Masalah Siswa SMA pada Hukum Archimedes - Rudi Purwanto (LP2M STIT Palapa Nusantara, 2020)
The purpose of this study was to explore the students’ problem solving skill to solve problem in Archimedes principle on the senior high school level. The method of this study was mixed method with explanatory follow up explanation design. The subject of this study was 30 students of k-11 in SMAN 9 Malang. The kuantitative data was collected through survey by 2 essay questions with reliability cronbah alpha 0,70. The qualitative data was collected through interview after analyze student answare. The aim of this interview was to follow up the pattern of student answare. The result of this study shown that students’ expert attitude began solve problem through definite problem qualitatively. In addition, the students’ novice attitude refer to not describe a problem qualitatively.